Arabic Scrambled Card Games for Vocabulary Mastery: An Experimental Study at The New College, Chennai - Dr K M A AHAMED ZUBAIR (RADINKA JAYA UTAMA PUBLISHER, PADANG< INDONESIA, 2026)
This study investigates the effectiveness of a modified card game,